Progress benchmarking and test system to manage competitive fitness in Para sports - Baryaev, A. A.; Abalyan, A. G.; Fomichenko, T. G. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to develop and scientifically substantiate a new progress benchmarking and test system for Para sports.